Performance evaluation of emergency department physicians using robust value‐based additive efficiency model - Labijak‐Kowalska, Anna (2021)
We propose a novel variant of the value-based additive data envelopment analysis model. It conducts a comprehensive robustness analysis of efficiency outcomes for all feasible input and output weights using mathematical programming and the Monte Carlo simulation. We also introduce the original procedures for selecting a common vector of weights and an approach for investigating the stability of results in a multiscenario setting. The presented framework is applied to evaluate the performance of emergency department physicians using data from the Children’s Hospital of Eastern Ontario in Ottawa. Our focus is on the physicians’ performance when dealing with groups of patients’ complaints related to abdominal pain and constipation, fever, extremity injury, head injury, and laceration/puncture. The obtained results emphasize the strong dependence of the physicians’ performances on the selected weight vectors. However, they prove helpful in pointing out overall good performers who can serve as universal benchmarks or niche performers being markedly better in providing care to a given complaint group. They also offer a basis for developing an improvement plan for the underperforming physicians, identifying the priorities for a practice-oriented model, and recognizing the most challenging patients’ complaints.